Short Communication: Lack of differentiation within the bigeye tuna population of Indonesia - NI PUTU DIAN PERTIWI; BUDI NUGRAHA; RIRIK KARTIKA SULISTYANINGSIH; IRWAN JATMIKO; ANDRIANUS SEMBIRING; ANGKA MAHARDINI; NI KADEK DITA CAHYANI; AJI WAHYU ANGGORO; HAWIS H. MADDUPPA; PAUL H. BARBER; GUSTI NGURAH MAHARDIKA (Society for Indonesian Biodiversity, 2017)
Pertiwi NPD, Nugraha B, Kartika R, Sulistyaningsih RK, Jatmiko I, Sembiring A, Mahardini A, Cahyani NKD, Anggoro AW, Madduppa HH, Ambariyanto A, Barber PH, Mahardika GN. 2017. Short Communication: Lack of differentiation within the bigeye tuna population of Indonesia. Biodiversitas 18: 1406-1413. All highly migratory tuna and tuna-like species have vast feeding grounds and spawning grounds. Indonesia’s tuna catch is the largest in the world. However, genetic diversity in the population structure within particular tuna species in Indonesia is very limited. Here we provide genetic data for bigeye tuna (Thunnus obesus) covering fishing grounds and local fish markets throughout Indonesia. A fragment of mitochondrial DNA in the D-loop control region was amplified from samples collected across Indonesia in the biennium 2012-2013. The results showed high haplotype diversity and low nucleotide diversity in our samples. Little differentiation occured between the eleven diverse sampling locations, nor was any separation detected between general regions of Indonesia, nor between samples from fishing grounds and samples from fish markets.